1995
DOI: 10.1152/jn.1995.74.5.2065
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of dorsal horn cell receptive fields following limited deafferentation

Abstract: 1. To test the hypothesis that subtotal deafferentation of dorsal horn cells can stimulate plastic changes in their receptive fields (RFs), diffuse deafferentation of the cat hindlimb dorsal horn was produced by transection of L7 or L6 and L7 dorsal roots. The following single-unit cutaneous low-threshold mechanoreceptor RF properties were compared between operated and control dorsal horns: 1) distance of RF center from tips of toes, 2) RF length-width ratio; and 3) RF area. 2. In both L7 and L6-L7 rhizotomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It has also been reported in several studies on the spinal dorsal horn (e.g. Basbaum & Wall, 1979; Devor & Wall, 1981; Lisney, 1983; Koerber & Brown, 1995) but not in others (Brown, Brown, Fyffe & Pubols, 1983; Brown, Fyffe, Noble & Rowe, 1984; Wilson, 1987). In the present experiments, even if such somatotopic reorganization occurred in the short term within the cuneate nucleus in response to the neonatal median nerve injury, the reorganization may have been reversed during the 12–24 months that elapsed before our electrophysiological analysis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has also been reported in several studies on the spinal dorsal horn (e.g. Basbaum & Wall, 1979; Devor & Wall, 1981; Lisney, 1983; Koerber & Brown, 1995) but not in others (Brown, Brown, Fyffe & Pubols, 1983; Brown, Fyffe, Noble & Rowe, 1984; Wilson, 1987). In the present experiments, even if such somatotopic reorganization occurred in the short term within the cuneate nucleus in response to the neonatal median nerve injury, the reorganization may have been reversed during the 12–24 months that elapsed before our electrophysiological analysis.…”
Section: Discussionmentioning
confidence: 72%
“…However, the clinical assessments are often based on simple detection tasks and may not reveal more subtle discriminative disturbances that reflect impaired transmission and signalling, and which might result either from the incomplete anatomical regeneration of the peripheral nerve, or from some form of functional reorganization or ‘plasticity’ within the central pathways that has been reported to follow partial deafferentation brought about by nerve injury or local anaesthetic blockade (e.g. Dostrovsky, Millar & Wall, 1976; Lisney, 1983; Merzenich, Kaas, Wall, Nelson & Sur, 1983; Calford & Tweedale, 1988, 1990; Wall, Huerta & Kaas, 1992; Nicolelis, Lin, Woodward & Chapin, 1993; Pettit & Schwark, 1993; Koerber & Brown, 1995). The reorganization described involves an alteration in body maps at the levels of the dorsal horn, the dorsal column nuclei, thalamus and cortex, in which there is an expansion in the central representation of body regions around the zone of deafferentation into areas of the map that previously represented the deafferented body part.…”
mentioning
confidence: 99%
“…Although none of these studies investigated the whole hand grasp control (i.e., only two-digit pinch or three-digit grasp was employed), their findings revealed an impaired sensorimotor integration process following somatosensory feedback deprivation at peripheral levels. At corticospinal levels, neurophysiological studies suggested that cutaneous feedback deprivation decreases the activation of motor neurons in several parts of the central nervous system (Rossini et al, 1996; Rossi et al, 1998), such as the dorsal horn of the spinal cord (Koerber and Brown, 1995), thalamus (Nicolelis et al, 1993; Rasmusson, 1996), and the cerebral cortex (Wall et al, 1986). However, most previous studies focused on the effect of local afferent abnormalities on adaptive peripheral behavioral and central processing changes, and none of them addressed the following questions: (1) how the disturbed and intact sensory input integrate and interact with each other to modulate the motor program execution; and (2) whether the motor coordination based on motor output variability presents between affected and non-affected elements (e.g., digits) and becomes interfered by the local sensory deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Rostrocaudal (RC) and mediolateral (ML) recording locations were expressed in normalized form, as fractional segmental and mediolateral locations (e.g., RC ϭ L 7.24 , ML ϭ 0.36, for a site 0.24ϫ the distance from the rostral to the caudal end of L 7 , 0.36ϫ the distance from the medial to the lateral edge of the dorsal horn). The recording locations and RFs of the single units were added to our database of 551 cells (Koerber et al, 1993;Koerber and Brown, 1995;Wang et al, 1997;Brown et al, 1998) for purposes of modeling somatotopy. This was accomplished by recalculating the descriptive model of the lamina III-IV cells including the new cell data.…”
Section: Single-unit Recordingmentioning
confidence: 99%